Variants of the Ekeland Variational Principle for a set-valued map involving the Clarke Normal Cone - Ha, Truong Xuan Duc (Journal of mathematical analysis and applications, 2006)
In this paper we present two set-valued variants of the Ekeland variational principle involving the Clarke normal cone and establish sufficient conditions for a set-valued map to have a weak minimizer or a properly positive minimizer when it satisfies Palais–Smale type conditions.